Quiet quitting and manager’s ability to motivate in the context of a manufacturing company - Vacek, Jakub; Hořáková, Marie; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Quiet quitting is a new term gaining a lot of traction on the internet and with the HR community. The term refers to the behaviour of not putting any extra effort into one’s job. So far, the consensus is that this behaviour is neither the fault of an employee nor a manager, but rather a mix of both. The research aims to discover how managerial techniques influence quiet quitting and the underlying reasons causing this behaviour. By analysing interviews conducted with both managers and employees of Serena Group, the research has gained more understanding of the studied behaviour and has identified the main factors influencing it. These factors were: a lack of resources, clarity of expectations, and planning structure. Additionally, the most successful managerial techniques were highlighted. Based on the findings, the thesis concludes with recommendations for managers.
Vedoucí práce: Marie Hořáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses